Rantai Nilai Global Manufaktur Tiongkok Pasca-COVID-19: Analisis Input-Output dan Implikasi Strategis bagi Indonesia - Fadhillah Akbar Salam; Reza Triarda (Cendekia Niaga, 2026)
The global supply chain is a crucial aspect of the dynamics of the global value chain within the manufacturing sector. China is known as the "world's factory" due to its ability to integrate inputs from around the world to produce high-value export products. The COVID-19 pandemic has severely impacted various economies and creating difficulties and shifts in production networks. Based on this, the research question is, "How has the input-output structure of the global value chain changed in China's manufacturing sector post-COVID-19; and its relationship to trade/manufacturing in Indonesia" This research uses a descriptive qualitative method with an input-output analysis approach within the global value chain (GVC) framework to understand how China's manufacturing sector has undergone structural changes post-COVID-19, and its impact and strategic recommendations for Indonesia. The discussion concludes that post-pandemic, starting in 2023, China has faced shifts in its global supply chain due to geopolitical factors, strict regulations, and global companies' efforts to diversify production to other countries. China's supply chain has demonstrated resilience by continuing to innovate technologically and diversify internally, while remaining a key player in the production of certain goods. China is seeking to strengthen its dominance in high-value industries like electric vehicles (EVs) and solar energy, not just mass manufacturing. This shift is more about "de-risking" than "decoupling" from China, as many supply chains still rely on raw materials or components from China. Indonesia's manufacturing linkage with China's global value chain post-pandemic takes the form of dependence on upstream inputs (raw materials and capital goods). Indonesia positions itself as a strategic partner for China by providing raw materials through forward linkages (increased downstreaming) and relying on Chinese raw material/capital inputs through backward linkages.Based on the situation in 2026, the strategic recommendations for Indonesian Manufacturing to overcome the challenges are: The main strategy is to "not separate itself from trade relations with China", but rather "change its position" from being just an upstream raw material importer to a balanced production partner by increasing the capacity of the domestic upstream and downstream industries.